Associations of serum carotenoid concentrations and fruit or vegetable consumption with serum insulin-like growth factor (IGF)-1 and IGF binding protein-3 concentrations in the Third National Health and Nutrition Examination Survey (NHANES III) - Anja Diener; Sabine Rohrmann (Journal of Nutritional Science, 2016)
Dietary intervention may alter the insulin-like growth factor (IGF) system and thereby cancer risk. In a qualitative review, eleven of twenty studies showed a link between one or more carotenoids, vegetable or fruit intake and the IGF system, however, with partly contrary findings, such that no firm conclusion can be drawn. Therefore, we evaluated associations between serum carotenoid concentrations or the intake of fruits and vegetables with IGF-1, IGF binding protein (BP)-3 and their molar ratio (IGF-1:IGFBP-3) within the Third National Health and Nutrition Examination Survey (NHANES III, 1988–1994). In our analysis, we included 6061 NHANES III participants and used multivariable-adjusted linear regression models. IGF-1 concentrations were significantly positively associated with serum concentrations of lycopene, β-carotene, α-carotene, β-cryptoxanthin and lutein/zeaxanthin in men and women. Statistically significant positive associations were observed for serum concentrations of α-carotene and lutein/zeaxanthin and intake of fruits with serum IGFBP-3 concentrations in women, but not in men. The IGF-1:IGFBP-3 molar ratio was significantly positively associated with serum concentrations of lycopene, β-carotene and α-carotene in men and with β-carotene in women. In conclusion, dietary interventions with carotenoids, fruits and vegetables may affect the IGF system, although the direction of these effects is currently unclear.